The Effect of Kolb's Learning Cycle on Students' Critical Thinking Skills (PRISMA, Prosiding Seminar Nasional Matematika, 2023)
The Kolb’s Learning Cycle involves acquiring abstract concepts that can be applied flexibly in a variety of situations. Basically involves four stages, namely: concrete learning, reflective observation, abstract conceptualization, and active experimentation. The purpose of this study is to determine the effect of Kolb’s learning cycle on students’ critical thinking skills. This research uses a literacy study approach. When conducting experiments is very important in the development of critical knowledge construction. Furthermore, the findings show that there are differences in the critical abilities of students who apply the Kolb’s learning cycle learning style and those who do not. Therefore, there is an effect of Kolb’s learning cycle learning style on students’ critical thinking skill. Further research is recommended, to understand why students with Kolb’s Learning Cycle learning styles and do not have different levels of critical thinking skills.